The Local Impact of Mining in Peruvian Districts: Evidence of a Subnational Resource Curse? - Fridtjof Bahlburg (International Journal of Energy Economics and Policy, 2023)
In the early 2000s, Peru experienced a major mining boom as global prices skyrocketed. At the same time, the country implemented a revenue-sharing arrangement between the national government and subnational governments, to redistribute the newly gained financial windfalls. Using census as well as survey data, we compare producing and non-producing districts in order to determine the effects of mining transfers on local development. We find evidence that producing districts were characterized by better development than non-producing districts before the establishment of a transfer of mining rents (the so-called Canon Minero). These effects persist when comparing districts over time. Concerning the effect of Canon Minero transfers on local development, we find that these transfers, through district governments’ expenditures, contribute to a reduced poverty rate and increased per capita consumption when comparing producing as well as non-producing districts in producing provinces to non-producing districts in non-producing provinces.